PENGARUH GAYA KEPEMIMPINAN KEPALA RUANGAN TERHADAP KEPUASAN KERJA PERAWAT DI HOSPITAL REFERAL RAEAO OE-CUSSE TIMOR-LESTE - Patricio Mariano Marques; Appolonaris Tomas Berkanis; Fepyani Tresna Feoh (CHMK HEALTH JOURNAL, 2021)
ABSTRACT Nurse job satisfaction is a very important element that affects nursing services in the hospital. One of the factors that affect the job satisfaction of nurses is the leadership style applied by the head of the room in leading and coordinating nurses in carrying out nursing care.The purpose of this study was to determine the effect of the leadership style of the head of the room on job satisfaction of nurses at Referal Hospital Raeao Oe-cusse Timor-Leste. This research is a quantitative study with a comparative analytic research design using a cross sectional approach. The sample in this study amounted to 39 nurses at the Referal Hospital Raeao Oe-cusse Timor-Leste who were taken using a total sampling technique. Collecting data using a questionnaire of the head of the room leadership style and job satisfaction of the nurses. The results showed that most respondents rated the leadership style of the head of the room in a good category, namely 18 people (46.2%), most of the respondents had job satisfaction in the satisfied category of 26 people (66.7%). The results of the Chi-square test prove that there is a significant influence between the leadership style of the head of the room on the job satisfaction of nurses with p value = 0.003 (α <0.05). It is hoped that the head of the room can apply a good leadership style so that the nurses are satisfied in their work so that good nursing services are created.Keyword: Leadership Style, Nurse Job Satisfaction